Number of positive radiographic findings in pediatric trauma patients - Ruffing, Thomas; Danko, Tim; Henzler, Thomas; Weiß, Christel; Hofmann, Alexander; Muhm, Markus Joachim (Emergency radiology, 2017)
Purpose: Conventional radiography is frequently performed in pediatric patients in whom fractures and dislocations are suspected. However, until now, the rate of positive findings of the most commonly performed radiographic examinations in pediatric patients is unknown. The aim of this study was to evaluate the number of positive findings in the 20 most frequently requested standard radiographic examinations in pediatric patients in a level 1 trauma center systematically.MethodsA transversal cohort study was conducted at a level 1 trauma center in Germany (2008-2014). In a statistical pre hoc analysis, a sample size of 200 images of each standard radiograph was determined. The picture archiving and communication system (PACS) was searched for radiographic examinations in patients under 18 years.ResultsThe following fracture rates for the investigated 20 most common examinations were found: 70.5% clavicle, 54.5% forearm, 53% wrist, 41.5% elbow, 30.5% lower leg, 20% hand, 18.5% finger, 12.5% toe, 12% forefoot, 11.5% ankle, 9% shoulder, 6.5% patella, 5.5% foot, 4% knee, 2% conventional rib series, 1.5% lumbar spine, 1% Towne view, 0.5% skull, 0% cervical spine, and 0% odontoid. Differences in the mean age of analyzed pediatric trauma patients in correlation to different standard radiographs were found.Conclusions: In our study, a relevant amount of different standard radiographs revealed a low fracture rate. Therefore, indications for X-ray should be checked properly and alternative procedures should be discussed with the patient and the parents. Clinical decision rules should be developed and pathways have to be implemented to minimize radiation exposure, waiting time, and costs.
Gesehen am 09.05.2018